Abstracte schilderkunst in België 1920-1970. - Alechinsky, Pierre; Baugniet, Marcel-Louis; Bury, Pol; Delahaut, Jo; Dypréau, Jean; Elno, J.; Narmon, François; Peeters, Jozef; Roberts-Jones, Philippe; Seaux, Jean; Servranckx, Victor; Vantongerloo, Georges; et al. (Brussel : Gemeentekrediet Brussel, 1996)
Alechinsky, Pierre ; Van Anderlecht, Englebert ; Antoine, Paul ; Barbaix, René ; Baugniet, Marcel-Louis ; Bergen, Emiel ; Bertrand, Gaston ; Beullens, André ; Blank, André ; De Boeck, Felix ; Boel, Maurice ; Bogaert, André ; Bogart, Bram ; Bonnet, Anne ; Vanden Borre, Guillaume ; Van Breedam, Camiel ; Burssens, Jan ; Bury, Pol ; Busine, Zephir ; Calonne, Jacques ; Carlier, Marie ; Carrey, Georges ; Closon, Henri-Jean ; Cobbaert, Jan ; Collignon, Georges ; Cortier, Amédée ; Daenens, Albert ; Decock, Gilbert ; Delahaut, Jo ; Donas, Marthe ; Van Dooren, Edmond ; Dorchy, Henri ; Dotremont, Christian ; Drybergh, Charles ; Dubail, Berthe ; Dubois, Jean ; Dudant, Roger ; Eemans, Marc ; Engel-Pak ; Flouquet, Pierre-Louis ; Gailliard, Jean-Jacques ; Gentils, Vic ; Greisch, Roger ; Grosemans, Arthur ; Guiette, René ; Heerbrandt, Henri ; Herregodts, Urbain ; Van Hoeydonck, Paul ; Holley, Francine ; Orix, Bill ; Joostens, Paul ; Jos ; Jung, Simonetta ; Kerels, Henri ; Kiemeneij, Jan ; Lacasse, Joseph ; Lacomblez, Jacques ; Landuyt, Octave ; Leblanc, Walter ; de Leeuw, Bert ; Lempereur-Haut, Marcel ; Lenaerts, Carlos ; Lewy, Kurt ; Van Lint, Louis ; Lismonde ; Lucas, Richard ; Maes, Karel ; Maeyer, Marcel ; Magritte, René ; Mara, Pol ; Matton, Jacques ; Meerbergen, Rudolf ; Mels, René ; Mendelson, Marc ; Michaux, Henri ; Milo, Jean ; Mortier, Antoine ; Noël, Victor ; Ongenae, Joseph ; Peeters, Jozef ; Peire, Luc ; Picon, José ; Plomteux, Léopold ; Quinet, Mig ; Raveel, Roger ; Renotte, Paul ; Rets, Jean ; de Sauvage, Guy ; Saverys, Jan ; Schmalzigaug, Jules ; Schrobiltgen, Paul ; Sempels, Geo ; Servranckx, Victor ; Seuphor, Michel ; Van Severen, Dan ; Staritsky, Anna ; Swimberghe, Gilbert ; Thienpont, Suzanne ; De Troyer, Prosper ; Ubac, Raoul ; etc.
biog. p. 183-206, selectieve bibliografie p. 207-211
Nederlands
Abstracte schilderkunst in België 1920-1970, Gemeentekrediet Brussel, 02.05.1996 - 07.07.1996
boek
Keywords: 20ste eeuw; België